B40 online business platform: e-commerce and life cycle model considerations - Abas, M. A. H.; Yassin, A. I. M.; Tahir, N. M.; Zabidi, A.; Ali, M. S. A. M. (UIKTEN - Association for Information Communication Technology Education and Science, 2021)
A new online business platform is needed in Malaysia. The proposed system aims to provide B40 household income group with the necessary knowledge for increasing readiness in online business, and equip them with access to available financing, e-commerce, and logistic solutions. Prior to project commencement, a review is performed on e-commerce and development life cycle models. The adopted approach includes issues such as client engagement, development team, duration of project, requirement of prototype, and scale of deployment. In this case, a modified Rapid Application Development model is suitable for monitoring project progress and delivery.